2018
DOI: 10.1039/c8gc01413b
|View full text |Cite
|
Sign up to set email alerts
|

In situ MnOx/N-doped carbon aerogels from cellulose as monolithic and highly efficient catalysts for the upgrading of bioderived aldehydes

Abstract: Cellulose-derived monolithic hierarchically porous MnOx/N-doped carbon aerogels exhibited excellent catalytic activity for the upgrading of lignocellulose-derived aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 55 publications
1
31
1
Order By: Relevance
“…4(a), all of the samples exhibited type IV isotherms but different H3 hysteresis loops at P/I 0 ranging from 0.45 to 1.0, from which it could be concluded that there existed both micropores and mesopores in all of the catalysts; thus, a porous structure developed in these obtained catalysts after being calcined. 23,24 This conclusion was further demonstrated in Fig. 4(b) as the sizes of these gained catalysts mainly ranged from 1 to 5 nm.…”
Section: Characterizationssupporting
confidence: 58%
“…4(a), all of the samples exhibited type IV isotherms but different H3 hysteresis loops at P/I 0 ranging from 0.45 to 1.0, from which it could be concluded that there existed both micropores and mesopores in all of the catalysts; thus, a porous structure developed in these obtained catalysts after being calcined. 23,24 This conclusion was further demonstrated in Fig. 4(b) as the sizes of these gained catalysts mainly ranged from 1 to 5 nm.…”
Section: Characterizationssupporting
confidence: 58%
“…In contrast, both Ag/PCNF‐600 and Ag/PCNF‐700 show very strong adsorption peaks within 50–150 °C, which can be attributed to weak basic sites associated with the chemical and physical adsorption of CO 2 . Moreover, weak peaks formed within 150–250 °C were correspondingly assigned to medium basic sites, which demonstrates the existence of the weak chemical adsorption of CO 2 . These results further indicated that pyrolysis temperature has an important influence on the formation of surface sites in the Ag/PCNF‐ T catalysts.…”
Section: Resultsmentioning
confidence: 83%
“…[29] Moreover,w eak peaks formed within 150-250 8Cw ere correspondingly assigned to mediumb asic sites, which demonstrates the existence of the weak chemical adsorption of CO 2 . [30] These results furtheri ndicated that pyrolysis temperature has an important influence on the formation of surface sites in the Ag/PCNF-T catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 4 c, the CTH reaction of furfural on O V ‐rich meso‐LMO shows a relatively high k value of 0.054. From the Arrhenius equation ln k =− E a / RT +ln A , the activation energy ( E a ) of the hydrogen transfer of furfural to FOL over O V ‐rich meso‐LMO catalyst was calculated to be 38.86 kJ mol −1 , which is advantageous than meso‐LMO (42.44 kJ mol −1 ), bulk LMO (49.29 kJ mol −1 ) and most reported catalysts (Supporting Information, Figure S7) [56, 57] . The low E a is attributed to well‐defined mesoporous structure and abundant oxygen vacancy active sites of O V ‐rich meso‐LMO catalyst.…”
Section: Resultsmentioning
confidence: 99%